Australian Aboriginal Identity: Being and/or Becoming - Polak, Iva (2008)
The paper focuses on the shifting signifier of Aboriginality as discussed by Aboriginal public intellectuals and writers from the publication of Aboriginal Writing Today in 1985 to the most recent anthology of essayist writing by Aboriginal Australians, Blacklines in 2003. The discussion shows initially simple bifurcation of Aboriginal identity on “ black” constructed in opposition to “ white” and a whole plethora of different and sometimes opposing views on defining contemporary Aboriginal identity from the 1990s onwards.
Projekt MZOS
ENG